2018
DOI: 10.1200/jgo.17.00146
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Carboplatin and Paclitaxel Chemotherapy Followed by Radiotherapy in High-Risk Endometrial Cancer: A Retrospective Analysis

Abstract: PurposeThe best adjuvant treatment in high-risk endometrial cancer remains unclear. Although adjuvant chemotherapy seems to improve overall survival (OS) in locally advanced disease, the role of adding radiotherapy is not certain. We evaluated the outcomes of patients with high-risk endometrial cancer treated with adjuvant chemotherapy followed by radiotherapy.Patients and MethodsWe performed a retrospective analysis of patients with high-risk endometrial cancer (endometrioid histology stages III to IVA or car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…External beam radiation (EBRT) or vaginal brachytherapy (VBT) can reduce vaginal stump recurrence, and EBRT is recommended for patients who are not eligible for chemotherapy ( 40 ). Some institutional studies have shown that both adjuvant chemotherapy and radiotherapy are found to be beneficial in CCC and UPSC patients ( 41 , 42 ), while other studies found that the patients treated with chemotherapy had no added benefit ( 43 , 44 ). There are no universally accepted guidelines for patient’s management ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…External beam radiation (EBRT) or vaginal brachytherapy (VBT) can reduce vaginal stump recurrence, and EBRT is recommended for patients who are not eligible for chemotherapy ( 40 ). Some institutional studies have shown that both adjuvant chemotherapy and radiotherapy are found to be beneficial in CCC and UPSC patients ( 41 , 42 ), while other studies found that the patients treated with chemotherapy had no added benefit ( 43 , 44 ). There are no universally accepted guidelines for patient’s management ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, metastatic endometrial carcinoma is treated with first-line chemotherapy consisting of carboplatin and paclitaxel [ 30 ]. Given our patient’s significant comorbidities, including paroxysmal atrial fibrillation and congestive heart failure with a reduced ejection fraction of 20%, as well as a poor ECOG performance status of 2, the decision was made to treat her with pembrolizumab as a first line.…”
Section: Discussionmentioning
confidence: 99%
“…Combination chemotherapy with carboplatin and paclitaxel has demonstrated good effects in the literature and is considered the first-line regimen (Bogani et al 2023). Though the literature is limited, there are some studies supporting the additional use of radiotherapy in high-risk endometrial cancer subtypes (Crane 2022;Cunha et al 2018). Immunotherapy also remains a good option, especially in individuals who don't respond to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%